1984
DOI: 10.1111/j.1600-0722.1984.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis as a precancerous condition

Abstract: Pindborg JJ, Murti PR, Bhonsle RB, Gupta PC, Daftary DK, Mehta FS: Oral submucous fibrosis as a precancerous condition. Scand J Dent Res 1984; 92: 224-9.Abstract -An evaluation of the malignant potential of submucous fibrosis, based on observations of 89 patients with the disease in Ernakulam District, Kerala, India was done. Out of the 89 patients, 12 were referred patients and 77 were diagnosed in population based studies. At the time of first examination oral cancer was found to be coexistent in nine (10%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(168 citation statements)
references
References 5 publications
5
156
1
Order By: Relevance
“…Incidence of malignant transformation of OSMF was found to be 4.23 % in the present study which is significantly higher than few studies carried out in the past, but is in conformity with the studies of Pindborg et al [19] in 1984, whereas less than the incidence found by Murti et al [14] in 1985. Both these studies were carried out in the Indian subcontinent, where betel nut chewing with or without tobacco is commonly seen in the society.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Incidence of malignant transformation of OSMF was found to be 4.23 % in the present study which is significantly higher than few studies carried out in the past, but is in conformity with the studies of Pindborg et al [19] in 1984, whereas less than the incidence found by Murti et al [14] in 1985. Both these studies were carried out in the Indian subcontinent, where betel nut chewing with or without tobacco is commonly seen in the society.…”
Section: Discussionsupporting
confidence: 90%
“…OSMF is also found to be associated with other premalignant lesions [14,19] like leukoplakia and erythroplakia and in the present study the incidence of the same was found to be 11 %. Normally in the OSMF, the oral mucous membrane is found to be severely atrophic and development of such lesions like leukoplakia and erythroplakia associated with acanthosis and proliferation of epithelial lining warrants serious thought and early intervention, as it could be a transition from fibrosis to a frank squamous cell carcinoma.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is a precancerous condition and about one third of these patients develop oral cancer. [1][2][3] We describe a patient with SMF who had an associated carcinoma of the hypopharynx, resulting in an unexpected difficult intubation.…”
Section: Objectif : Citer Un Cas D'intubation Difficile Inhabituel Sementioning
confidence: 99%
“…OSMF is a potentially malignant disorder with a malignant transformation rate of 2.3 to 7.6%. [2][3] The most common debilitating symptoms of OSMF are burning sensation in the mucosa and inability to open mouth which also has psychological and social implications for patients.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%